Pemanfaatan Wayang dari Bahan Kardus Bekas Sebagai Media Pembelajaran Di SDN Mekarsari (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2025)
This service is motivated by the understanding of the importance of character building and creativity for children in loving local culture, especially the art of wayang kulit, whose existence is increasingly forgotten by the current generation. The onslaught of the current era, the characters that appear on television, social media are often not in accordance with the period of their character formation and are not in accordance with the culture that has been formed by their predecessors, especially Javanese culture. Therefore, this service is important to be carried out with the aim of introducing characters in wayang and instilling creativity and a sense of love for their own culture. The hope with this service is that children understand and are able to emulate the characters of the figures in wayang. This activity was carried out at SDN 02 Mekarsari and SDN 03 Mekarsari, Cipari District, Cilacap Regency, with a target of 20 students. Based on the evaluation results, the service received a positive response and achieved satisfactory results, with indicators that students were able to follow the activities until the end and dared to make physical contact holding the wayang and were able to make wayang from cardboard in order to develop children's motor skills.